Eating behavior in patients with smell loss - Liu, David T.; Prem, Bernhard; Sharma, Gunjan; Kaiser, Julia; Besser, Gerold; Mueller, Christian A. (Frontiers in Nutrition, 2022)
Background: The objective of this study was to determine how clinical characteristics and validated quality of life (QoL)-measures are associated with eating behavior in patients with olfactory dysfunction (OD). Methods: For this cross-sectional study, 150 OD patients of different causes were retrospectively recruited. Olfactory function was measured using the Sniffin’ Sticks (TDI), while olfactory-related QoL was evaluated with the Questionnaire of Olfactory Dysfunction negative and positive statements (QOD-NS and QOD-PS). The importance of olfaction was measured using the Importance of Olfaction Questionnaire (IOQ). The Dutch Eating Behavior Questionnaire assessed eating behavior based on emotional, external, and restrained eating. Associations were sought between eating behavior metrics (as dependent variables) with clinical characteristics and olfactory-related outcome measures. Results: Emotional, external, and restrained eating behavior deviating from normative standards were reported in 54%, 71.3%, and 68% of patients, respectively. Multivariate regression modeling revealed that emotional eating was associated with age (ß=-0.227, p=0.032), the body mass index (BMI, ß=0.253, p=0.005), the TDI (ß=0.190, p=0.046), and the QOD-NS (ß=0.203, p=0.049). External eating was associated with OD duration (ß=0.291, p=0.005), the TDI (ß=0.225, p=0.018), the QOD-PS (ß=-0.282, p=0.008), and the IOQ (ß=0.277, p=0.004). Restrained eating was associated with age (ß=0.216, p=0.033), the BMI (ß=0.257, p=0.003), male gender (ß=-0.263, p=0.002), and the IOQ (ß=0.332, p<0.001). Conclusions: Clinical characteristics and olfactory outcome measures differentially impact eating styles in OD patients. Our study's results highlight the importance of considering unfavorable changes in eating behavior during clinical counseling.